Spatio-temporal Variation of Meteorological Influence on PM2.5 and PM10 over Major Urban Cities of Bangladesh - Nafisa Islam; Tarik Reza Toha; Mohammad Maksimul Islam; Tanvir Ahmed (Aerosol and Air Quality Research)
Abstract A detrended seasonal analysis on a 6-year (2013–2018) dataset of daily Particulate Matter (PM) concentration and meteorological parameters is performed to understand the spatio-temporal variation of PM and the seasonal influence of meteorological factors on PM pollution over 6 major urban cities of Bangladesh. Cross-correlation and multiple non-linear regression (MNLR) of air quality and meteorological data were used to explore the meteorology-PM interactions and their spatio-temporal variability. Meteorological influence on PM was found to be stronger in the southern part of the country relative to the northwestern part. MNLR analysis implied that meteorological parameters could explain up to 39% of daily PM variability during high pollution days. The deposition effect of relative humidity was prominent during the premonsoon season, while rainfall impact becomes dominant in the monsoon season, specifically in the northeastern region. Wind speed was observed to have a dilatory effect on PM variation, although wind seemed to carry sea aerosol in southern regions. In addition, the northwestern wind appeared to contribute to PM rise in most urban areas by carrying PM loading. In winter, the low temperature was found to favor PM accumulation, while in monsoon, high temperature causes PM rise, possibly by assisting atmospheric secondary aerosol formation. Solar radiation positively influenced atmospheric PM formation, and the influence was stronger in the northwestern region. It is shown that meteorological parameters influence the seasonal variability of PM, but the extent of this influence varies depending on temporal and regional factors.